Using Molecular Evidence in Sediments to Interpret Historical Archives - Kissinger, Jennifer (Université d'Ottawa | University of Ottawa, 2024)
The main objective of this dissertation is to develop new applications in palaeolimnology, the study of sediment cores as archives to track historical sequences of events. This dissertation is intended to expand the utility of palaeolimnology to examine relationships between humans and the environment. Here I use lake and pond sediments from eastern Canada as natural archives to: (1) differentiate between sources of organic inputs to determine anthropogenic influences on historical lake eutrophication using multiple lines of independent evidence; (2) analyze sedimentary ancient DNA using a nascent analytical method in the eastern Canadian Arctic at ponds adjacent to archaeological sites; and (3) investigate advanced sedimentary analysis in Paleo-Inuit and Thule-Inuit affected sites incorporating isotope ratios, lipid biomarkers, and sedimentary ancient DNA. CHAPTER TWO is a published manuscript reporting on the use of lake sediments to trace and differentiate between sources of freshwater lake eutrophication. This study was commissioned to examine sources of water pollution in the southwestern region of Nova Scotia where multiple potential anthropogenic pressures coexist and showed that several sediment markers (including δ¹⁵N, cholesterol, β-sitosterol, As, Cu, and Se) together track historical contamination from local animal husbandry. CHAPTER THREE investigates the application of sedimentary ancient DNA analysis to trace ancient human occupation at these sites through hunting and subsistence patterns reflected in the environmental DNA from terrestrial fauna, marine fauna, and insects as part of a multiproxy analysis including isotope ratios and lipid biomarkers. Results showed a multitude of changes to the fauna sedimentary ancient record during Paleo-Inuit and Thule-Inuit occupation, including a marked turnover from muskox (Ovibos moschatus) and northern collared lemming (Dicrostonyx groenlandicus) to caribou (Rangifer tarandus). Sedimentary ancient DNA from bowhead whale (Baleana mysticetus) and wolf/dog (Canis lupus) appear during periods of human occupation and suggest these taxa may have been more relevant to the Paleo-Inuit than originally understood. The presence of sedimentary ancient DNA from certain insect taxa during human occupation, such as Diptera and Termitidae, may reflect human sustenance and husbandry activities and offers promise that environmental DNA from these organisms with small biomass can be identified in eastern Arctic sediments. CHAPTER FOUR examines anthropogenic influences in the catchment through sedimentary ancient DNA analysis of flora, moss, algae, and bacteria. In sediments with a history of ancient human occupation the sedimentary ancient DNA of wastewater indicator taxa from flowering plants, such as buttercups (Ranunculus), and bacteria, Burkholderiales and Gammaproteobacteria, appear during periods of human occupation coeval with cultural eutrophication. Cyanobacteria (including Synechococcaceae and Nostocales) sedimentary ancient DNA appears in sediments with a history of human occupation coeval with cultural eutrophication and in reference sediments only during 20th century warming. A marked turnover from the sedimentary ancient DNA of freshwater and brackish algae taxa to seaweed (Oophila, Monoraphidium contortum, and Jenufa perforata to Caulerpa) during the height of whaling activities in human occupied sediments reflects an ecosystem markedly impacted by historical human activities. Collectively, this research suggests these indicators can be used in eastern Arctic sediments to reconstruct human occupation and supports further study related to the taphonomy of sediments and soils in lacustrine environments. In sum, these studies demonstrate that sedimentary archives track a multitude of historical events and human activities in combination with traditional evidence and provide context and insight to the understanding of modern and ancient ecology, providing new possibilities for forensic investigations, archaeology, and palaeoecology in the Arctic and elsewhere.
Keywords: molecular evidence; forensic science; trace analysis; molecular biogeochemistry; isotopes; sedimentary ancient DNA (sedaDNA); lipid biomarkers; molecular archaeology